2017
DOI: 10.1002/adma.201604223
|View full text |Cite
|
Sign up to set email alerts
|

Inheriting the Characteristics of TADF Small Molecule by Side‐Chain Engineering Strategy to Enable Bluish‐Green Polymers with High PLQYs up to 74% and External Quantum Efficiency over 16% in Light‐Emitting Diodes

Abstract: Thermally activated delayed fluorescence (TADF) polymers are designed and synthesized by grafting the TADF emitter to the side chain of the polycarbazole backbone. By employing these TADF polymers with large ratio of delayed fluorescence component and high photoluminescence quantum yield as the emitters, the solution-processed light-emitting diodes achieve a maximal external quantum efficiency of 16.1% at a luminance of around 100 cd m .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
114
1
1

Year Published

2017
2017
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 212 publications
(118 citation statements)
references
References 36 publications
2
114
1
1
Order By: Relevance
“…With the increase of the TADF units in the copolymer, the emission of the polycarbazole ( PCzDP‐n ) decreased significantly, which suggested efficient energy transfer from the main chain to the TADF unit, and all these polymers exhibited high PLQY of up to 74% in the film. By utilizing the TADF polymeric emitters in solution‐processed OLED devices with the structure of ITO/PEDOT:PSS (50 nm)/emitting layer (EML) (70 nm)/TmPyPB (40 nm)/Liq (1 nm)/Al (100 nm), a significantly higher maximum EQE of 16.1% of bluish‐green emission could be obtained proving this as a very valid design concept …”
Section: Tadf Polymersmentioning
confidence: 96%
See 1 more Smart Citation
“…With the increase of the TADF units in the copolymer, the emission of the polycarbazole ( PCzDP‐n ) decreased significantly, which suggested efficient energy transfer from the main chain to the TADF unit, and all these polymers exhibited high PLQY of up to 74% in the film. By utilizing the TADF polymeric emitters in solution‐processed OLED devices with the structure of ITO/PEDOT:PSS (50 nm)/emitting layer (EML) (70 nm)/TmPyPB (40 nm)/Liq (1 nm)/Al (100 nm), a significantly higher maximum EQE of 16.1% of bluish‐green emission could be obtained proving this as a very valid design concept …”
Section: Tadf Polymersmentioning
confidence: 96%
“…In further research, the authors refined this concept by using the TADF D–A monomer 10‐(4‐((4‐(3,6‐dibromo‐9H‐carbazol‐9‐yl)phenyl)sulfonyl)phenyl)‐10 H ‐phenoxazine ( PXZ‐DP‐BrCz ) together with other two non‐TADF comonomers ( Figure ) . As derived from density functional theory (DFT) calculation, the LUMOs of the resulting copolymer are mainly located on the diphenyl sulfone moiety, while the HOMOs are located at the electron donor of phenoxazine, exhibiting electronic separation from the main chain of polycarbazole.…”
Section: Tadf Polymersmentioning
confidence: 99%
“…Polymers, in contrast, can have both good thermal stability, solution processable and facile functionality to introduction of various functional units into pendant groups . Nowadays, polymeric materials have been proven to be ideal emissive materials for the solution‐processed devices .…”
Section: Introductionmentioning
confidence: 99%
“…77 Intuitively, TADF polymers should be based on a non-conjugated backbone to prevent triplet trap formation as triplet energy has been known to decrease rapidly with increasing effective conjugation length. 79,82 However, there have been several reports of conjugated TADF polymers with chromophores either grafted 83,84 or built-in along the polymer main-chain [85][86][87], and most of them performed nicely in PLED devices (EQE: 2.2-16.1%). Wei et al recently demonstrated how a TADF-inactive carbazole-based monomer could be turned into a TADF-active macromolecule (macrocycle or polymer).…”
Section: Thermally Activated Delayed Fluorescence (Tadf) Polymersmentioning
confidence: 99%
“…118 On the other hand, the best non-conjugated TADF polymer (TADF-P2) offered a green PLED (k EL at 533 nm) with an EQE of 20.1% 21, whereas the conjugated counterpart (PCzDP-10) gave a PLED with a blue emission at 496 nm and an EQE of 16.1%. 83 Therefore, it is reasonable to conclude that for these two classes of polymers (phosphorescent and TADF), the nature of the polymer backbone has minimal impact on the PLED performance.…”
Section: Conjugated Versus Non-conjugated Polymers: Pled Performancesmentioning
confidence: 99%